Efeito dos anúncios de fusões e aquisições no retorno acionista de empresas portuguesas - Lobo, Bruno Filipe Silva (2022)
Mergers and / or acquisitions (M&A) are important business operations that can help companies diversify their businesses, in order to become stronger and more competitive. Most of these operations take place in international markets and between large companies, being the main object of present scientific research. The main objective of this dissertation is to investigate the impact of the announcement of M&A transactions, which have occurred between Portuguese companies since 2000, in the quotation of the respective shares, namely in terms of abnormal returns. The empirical study involves 29 integration operations and the methodology used is that of the study of events. The models proposed by Beaver and Mackinlay were applied to answer the research questions. The results suggest that M&A transactions cause the offering companies to accumulate negative average abnormal returns slightly higher than the average positive abnormal returns over an extended period. Regarding the target companies, the net loss was more pronounced. However, in a more circumscribed analysis, the impact of the news and the accumulation of abnormal returns are clearly identified. The evidence also indicates that the abnormal returns of companies involved in restructuring operations tend to disappear about a week after the announcement date and that they tend to stabilize more quickly in the targeted companies. Moreover, the empirical work also demonstrates that the integration operations provoke strong reactions in the returns of the companies involved. These impacts were more intense in the target companies, especially on the date of the announcement of the operation, with the creation of statistically significant value.